POTENTIAL PRODUCTIVITY OF LAMTORO ACCESSIONS AS FORAGES - Handayani, Dwi Pangesti; Ayunisa, Wenny; Nawfetrias, Winda; Juwartina, -; Royani, Ida (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 10 No 2 (2021): Pastura Vol. 10 No. 2 Tahun 2021DO - 10.24843/Pastura.2021.v10.i02.p02, 2021)
Lamtoro (Leucaena leucocephala L.) is a fibrous plant for animal feed with young leaves and stems as edible portions. Every region has their own morphological diversity and potential productivity. The aim of this study was to determine the potential of lamtoro accessions as a forage based on morphological performance and weight of edible portion. The experiment was arranged in a randomized block design with three levels of lamtoro accessions (NTT, Yogyakarta, Serpong) and eight replications. The results showed that lamtoro accessions significantly affected for plant height, wet weight and dry weight of edible portion. Based on the performance of plant morphology it showed that the accession of Serpong can be used as forage for feeding with human assistance, while accessions for NTT and Yogyakarta potential to be forages for grazing. Keyword: forages, lamtoro accession, potential productivity